Study of Antimicrobial Activity of Natural Plant Oils against Bacterial Species Isolated From Hospital Sample - Yadav, Nishu (International Journal of Pharmaceutical & Biological Archive, 2012)
Study of Antimicrobial Activity of Natural Plant Oils against Bacterial Species Isolated From Hospital Sample